2020
DOI: 10.1021/acsomega.0c03184
|View full text |Cite
|
Sign up to set email alerts
|

N-Substituted Phenothiazines as Environmentally Friendly Hole-Transporting Materials for Low-Cost and Highly Stable Halide Perovskite Solar Cells

Abstract: Most of the high-performing halide perovskite solar cells (PSCs) leverage toxic chlorinated solvents (e.g., o -dichlorobenzene or chlorobenzene) for the hole-transporting material (HTM) processing and/or antisolvents in the perovskite film fabrication. To minimize the environmental and health-related hazards, it is highly desirable, yet at the same time demanding, to develop HTMs and perovskite deposition processes relying on nonhalogenated solvents. In this work, we designed two small m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…The TPA moieties feature a non-planar geometry that confers unique hole transport properties, while the PTZ unit has an electron-donating butterfly structure, suitable for several kinds of functionalization, which allows the formation of stable radical cations. [14][15][16][17][18][19][20][21][22][23][24][25][26] HTMs designed from a combination of TPA and PTZ moieties, e.g. PTZ2 reported by Grisorio et al, 26 have shown efficiencies comparable to those obtained with Spiro-OMeTAD.…”
Section: Introductionmentioning
confidence: 94%
“…The TPA moieties feature a non-planar geometry that confers unique hole transport properties, while the PTZ unit has an electron-donating butterfly structure, suitable for several kinds of functionalization, which allows the formation of stable radical cations. [14][15][16][17][18][19][20][21][22][23][24][25][26] HTMs designed from a combination of TPA and PTZ moieties, e.g. PTZ2 reported by Grisorio et al, 26 have shown efficiencies comparable to those obtained with Spiro-OMeTAD.…”
Section: Introductionmentioning
confidence: 94%
“…The utilization of azomethine denoted as MS-2 with double 4-[N,Ndi(4-methoxyphenyl)amino]phenyl units as HTM in devices with the structure FTO/bl-TiO 2 /mp-TiO 2 /CH 3 NH 3 PbI 3 /MS-2/Au allowed for obtaining a PCE of 6.68% [ 45 ]. Salunke et al [ 46 , 47 ] reported a series of imines with phenothiazine core end-capped with the TPA unit. The fabricated PSCs (ITO/SnO 2 /Cs 0 .…”
Section: Introductionmentioning
confidence: 99%
“…The phenothiazine unit was introduced to form the main chain; this phenothiazinebased polymer possesses considerable electron-donating ability due to its heteroaromatic units. 22,23,26 The triarylamine functional group was attached to the phenothiazine units as side chains, which provided fascinating hole-transport capability. 27,28 We further functionalized the triarylamine group with a methoxy group, adjusting the HOMO energy level of PPZ-TPA to a deeper level and enhancing the ability to attract holes.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The phenothiazine-based polymers with cost-effective phenothiazine raw material and the versatile reactive sites exhibit striking advantages, which affords the ingress into the commercial production of HTMs due to their facile synthesis strategy . In addition, it has been verified that sulfur-based heterocycles in HTMs could serve as a Lewis base to passivate the surface defects of perovskite films. , Herein, we synthesize a new triarylamine functionalized phenothiazine polymeric HTL, named poly­[4-(10H-phenothiazin-10-yl)- N , N -bis­(4-methoxyphenyl)­aniline] (PPZ-TPA), which has moderate hole mobility and suitable band alignment for efficient hole extraction and transport.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation